A STUDY ON THE IDENTITY AND ROLE OF NARRATORS IN MAHAKABI ANGANGHAL’S KHAMBA THOIBI SEIRENG - Singh, Mutum Shanta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper tries to examine the role of narrators in Mahakabi Anganghal’s Manipuri epic, Khamba-Thoibi Seireng with the intention to study the epic as a narrative text by analyzing it through the theoretical framework of narratology. In the epic, there is the presence of both the ‘primary external narrator’ and the ‘internal narrator’ who narrate the immortal love story of Khamba and Thoibi. The ‘primary external narrator’ narrates the events of things or situations from outside the world of the story as the narrator of the main story whereas the narrations of the characters serve as ‘internal narrators’ who maintain the continuity and flow of the story. The omniscient narrator of the epic serves as the primary narrator and narrates the story of the parentage of Khamba and Khamnu, the legendary story of Kunjamala in the form of a digression etc. the main characters like Khamba, Khamnu, Thoibi etc. serve as internal narrators who narrate the stories associated with their lives through analepsis.